Contagious itch and disgust during a lecture on ectoparasitic infestations: Two co‐activated complementary parasite defense systems?. Issue 6 (5th November 2020) - Kamber, Marise S.; Sutter, Mia; Navarini, Alexander; Mueller, Simon M.
Abstract: (Audio‐)visual itch transmission is referred to as "contagious itch" (CI) and has been linked to an evolutionarily ingrained ectoparasite defense system. Disgust is considered to be part of the behavioral immune system aimed to prevent the spreading of pathogens. Although they probably serve a similar purpose, the relationship between CI and disgust is unknown. We investigated their co‐prevalence, correlation, and differences between the sexes and between skin‐diseased and skin‐healthy individuals. Medical students attending a lecture on ectoparasitic infestation indicated their change in itch and disgust compared to baseline on a 0 to 10 numerical rating scale (NRS) and specified which ectoparasitic infestation induced CI and disgust the most. Out of 132 participants, 87.9% reported CI, 84.1% disgust. The maximum intensity of CI was 3.68 ± 2.08 NRS ( P  < .0001), of disgust 3.80 ± 2.68 NRS ( P  < .0001), respectively. The CI and disgust correlated positively (rho 0.272; P = .002), but we also found that specific ectoparasitic infestations triggered rather itch than disgust and vice versa. Our results indicate that CI and disgust are coincident phenomena of distinct defense systems: CI is aimed to scrape off ectoparasites, disgust to prevent ingestion of pathogens. Furthermore, our data point to differences in CI and disgust between the sexes and skin‐healthy vs skin‐diseased participants.